Application of expert systems for determining the size of the sanitary protection zone of a nuclear facility - Barbashev, S.V. (Вопросы атомной науки и техники, 2021)
The dimensions of the sanitary protection zones (SPZ) for nuclear facility (NF) of I and II hazard classes are calculated based on the recommendations of national regulatory documents, taking into account the radiation factor of human exposure. At the same time, factors of a non-radiation nature are not considered, although they are present in the zone of influence of the NF and make an additional contribution to the formation of negative consequences for people. In this case, the definition of the boundaries of the SPZ is possible only in a result of analysis, comparison and calculation of various values characterizing the state of the environment and NF. Such an opportunity can be provided by the use of an expert system. The article describes a simplified version of the expert system designed to determine the boundaries of the NPP SPZ, which takes into account the dose criterion and criteria for non-radiation factors, and the results of its application for a real NPP.